2017
DOI: 10.1002/star.201700171
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Foxtail Millet Starch Film Incorporated with Clove Leaf Oil for the Packaging of Queso Blanco Cheese as a Model Food

Abstract: Clove leaf oil was incorporated into foxtail millet starch (FMS) for developing an active packaging material with antimicrobial and antioxidant activities. The FMS films that contained clove leaf oil exhibited changes in tensile strength (6.78–4.00 MPa) and elongation at break (66.26–99.48%) with the addition of increasing concentrations of the essential oil, and possessed ultraviolet‐light barrier properties. Moreover, the FMS films that contained clove leaf oil inhibited the growth of Listeria monocytogenes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…The production of radical species in the chicken sample was reduced by 50% regrading to control treatment on the 9th day [134]. Similar results were obtained in a starch film containing clove leaf oil for the packaging of cheese [135]. The addition of plant oil resulted in good film radical-scavenging activity and antimicrobial activity against Listeria monocytogenes as well.…”
Section: Starchsupporting
confidence: 71%
“…The production of radical species in the chicken sample was reduced by 50% regrading to control treatment on the 9th day [134]. Similar results were obtained in a starch film containing clove leaf oil for the packaging of cheese [135]. The addition of plant oil resulted in good film radical-scavenging activity and antimicrobial activity against Listeria monocytogenes as well.…”
Section: Starchsupporting
confidence: 71%
“…As presented in Table 3, the ABS film without CNE did not exhibit antioxidant property, whereas the antioxidant property of the films containing CNE was proportional to the amount of added CNE. Similarly, Yang et al [15] demonstrated that pure foxtail millet starch films had no antioxidant activity, but films with clove leaf oil showed increased ABTS and DPPH scavenging activities with increasing amounts of clove leaf oil. In this study, the ABS film containing 1% CNE showed the highest antioxidant activity, and the ABTS and DPPH scavenging activities were 100% and 94.9%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The physical properties of the ABS films were examined using a Testometric machine (250-2.5 CT, Testometric Co., Lancashire, UK). The water vapor permeability (WVP), water solubility (WS), and moisture content (MC) of the ABS films were measured as described by Yang et al [15]. Five replications were recorded independently.…”
Section: Methodsmentioning
confidence: 99%
“…Acerola extract, oregano oil, ginger oil, betel oil, mentha spicata oil, rosemarin oil, ziziphora clinopodioides oil, zataria multiflora oil, satureja plant oil, thyme oil, grape seed extract, eucalyptus oil [151,159,160,162,164-167,169-171, 173,200-202] Vegetables and fruits Litsea cubeba oil, clove and oregano oils, mentha spicata, cinnamon oil, limonene, thyme oil [91,114,153,156,178,199,203,204] Pastry and bread Garlic essential oil, pomegranate peel extract, cinnamon oil, clove oil [178,179,205] Dairy and cheese Clove leaf oil, ginger oil [107,126,176] Apricot kernels are a major agricultural waste. One possible utilization for them is to extract the essential oil from the bitter core.…”
Section: Meatmentioning
confidence: 99%